2018
DOI: 10.12991/jrp.2018.79
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer, Antioxidant Properties and Phenolic, Flavonoid Composition of Heracleum platytaenium Plant Methanolic Extracts

Abstract: ABSTRACT:Heracleum platytaenium is an edible herb and strongly aromatic plant that is endemic to Turkey. Although, a number of studies have been conducted on the components and composition of essential oils of the different parts of this species, its antioxidant, antiproliferative and /or cytotoxic proporties have never been explored. The present study aimed to evaluate total phenolic content (TPC), total flavonoid content (TFC), the antioxidant activity and anticancer properties of the methanolic extracts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…The study of Tulbaghia violacea on some cancer cell lines (HeLa, ME-180, MDA-MBA-231, and MCF-7) showed increased p53 expression until 40% on HeLa and 33% on ME180in treated cells (Astirin et al 2009). The study on methanol extract of flower and stem of H. platytaenium showed that both extracts inhibit T47-D cell lines cancer cell growth but not on MDA-MB-231 cells (Akillilar et al 2018). From both results, it appears that the extract M and TWN induced the decrease of expression of Bcl-2, a protein marker of cancer incidence followed by increased expression of protein p53, an apoptosis induction.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The study of Tulbaghia violacea on some cancer cell lines (HeLa, ME-180, MDA-MBA-231, and MCF-7) showed increased p53 expression until 40% on HeLa and 33% on ME180in treated cells (Astirin et al 2009). The study on methanol extract of flower and stem of H. platytaenium showed that both extracts inhibit T47-D cell lines cancer cell growth but not on MDA-MB-231 cells (Akillilar et al 2018). From both results, it appears that the extract M and TWN induced the decrease of expression of Bcl-2, a protein marker of cancer incidence followed by increased expression of protein p53, an apoptosis induction.…”
Section: Discussionmentioning
confidence: 93%
“…Herbal medicinal are usually used as sources of agents for traditional medicines for thousands of years. In recent years, natural products and their derivate became beneficial alternative therapy (Akillilar et al 2018). Artemisia is one of the well-known plants for its antimicrobial, insecticidal, antioxidant, and antimalarial ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover these molecules have disease-fighting potentials against several chronic and degenerative disorders including autoimmune, cardiovascular, dermatologic, neurodegenerative, ocular and respiratory system diseases and even aging and cancer [2][3][4][5]. Polyphenols and flavonoids, which are found in almost all fruits and vegetables, are natural antioxidant and anti-inflammatory compounds [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Екстракти Heracleum platytaenium, яка багата на фенольні сполуки та флавоноїди, інгібували активність GST на 38-47% і мали цитотоксичний ефект на клітини лінії раку молочної золози T47D (позитивна експресія рецепторів естрогену) (Telkoparan et al, 2018).…”
unclassified